Predictors of ICU Admission and Mortality in Patients with Coronavirus Disease in Community Hospitals in Virginia - Pathak, Vikas; Conklin, Courtney (Europasian Journal of Medical Sciences, 2022)
Background Coronavirus Disease 2019 (COVID-19) is caused by novel coronavirus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The mortality of patients in the Intensive Care Unit (ICU) is variable and has been reported to be as high as 80%. Not much is known about the factors leading to the progression of hospitalized patients to requiring ICU care and the predictors of mortality among ICU patients. We performed univariate followed by multivariate logistic regression analysis to determine predictors of progression of the disease and factors associated with mortality. Data and Methods Retrospective data were collected from 101 consecutive patients admitted from March, 2020 to June, 2020. Data were collected from five different community hospitals in eastern Virginia with varied demographics. Results A total of 101 consecutive hospitalized patients in five community hospitals in eastern Virginia were enrolled in the study. Out of the 101 patients, 53 were admitted into the ICU for respiratory failure. Of these 53, 40 patients required intubation and mechanical ventilation. Altogether, 30 of the 53 patients admitted to the ICU died. Of these 30 patients, 25 required intubations. Of these 25 patients, one had mild, 6 moderate and 18 severe Adult Respiratory Distress Syndrome (ARDS). Patients aged 60 years and above accounted for >2/3rd of the cases in ICU. Conclusion Patients with underlying conditions, elevated inflammatory markers, multi-organ failure and the need for mechanical ventilation were consistently associated with poor outcomes in patients with COVID-19.